The potential implications of autonomous vehicles in and around the workplace - Pettigrew, Simone; Fritschi, Lin; Norman, Richard (Molecular Diversity Preservation International (MDPI), 2018)
The advent of autonomous vehicles is forecast to bring enormous changes to the workplace as positions primarily involving driving become progressively redundant. Little is known about public awareness of these impending changes and the potential impacts on society and individuals. This study involved a national survey of Australians and interviews with key stakeholders across multiple countries to identify major potential issues associated with vehicle automation, including in and around the workplace. Most survey respondents had concerns relating to job losses in driving occupations, while almost half anticipated increased employment in technology-related areas. Three primary themes were evident in the data from the stakeholder interviews: (1) the inevitability of the universal use of AVs and hence the immediate need for labour market planning, (2) associated potential effects on occupations that are not primarily structured around driving, and (3) the possibility of increased worker safety and enhanced commuting opportunities.